Supporting Older Workers in the Context of Industry 4.0 Requirements - Andrzej GRABOWSKI (Wspomaganie starszych pracowników w kontekście wymagań Przemysłu 4.0, 2020)
The transformation involving the implementation of the concepts of Industry 4.0 can significantly change the labour market, presenting employees and employers with new challenges. Some of these challenges can be solved with the use of technological development, in particular through further robotisation. An interesting example of this phenomenon is the implementation of the concept of remote presence through the use of remotely controlled robots equipped with arms and cameras. This is important for older workers, including those with a muscle strength deficit. However, not all activities can be performed by robots. Some tasks still have to be performed by people. In the factories of the future, cognitive resource requirements may increase significantly. In this respect, appropriate training conducted using virtual reality can help.
Keywords: Wspomagania pracowników w kontekście Przemysłu 4.0